Desenho de plataforma digital de aplicação de sanções administrativas na prefeitura municipal de João Pessoa - Sousa, Alisson Albert Andrade de (2023)
The right to information was granted to Brazilian citizens and foreigners residing in the country, as a principle of public transparency, in accordance with the Federal Constitution of 1988. In the municipality of João Pessoa, capital of Paraíba, the Secretariat Municipal Executive for Public Transparency was created, in order to meet the principle of public transparency and the population's demand for information about municipal management. Thus, the relationship between governments and society, based on laws that aim to make public information available in real time through electronic means, precisely through institutional websites, generates significant changes. The research verifies a practical gap on the need to create a modern and efficient communication channel between population and management. Therefore, the creation of a digital platform design for the application of administrative sanctions in João Pessoa, positioning the praxis of active transparency, which is the one where information is disclosed to the population without needing to be requested, is configured as an alternative interesting access to information. The research objective was to develop a design of a digital platform for the application of administrative sanctions, to suppliers that celebrate administrative contracts in the city hall. Methodologically, we used a qualitative approach, with exploratory, descriptive, explanatory purposes and bibliographic and field research procedures using netnography. Considering the importance of an efficient and effective management process for organizations, in order to have a complete view of the entire process, we present the mapping of the administrative sanctions process and elaborate the flowchart. With the design of the Digital Platform for the Application of Administrative Sanctions, it was noticed that the more information made available by the authorities that hold the information, the better it will be for managers to make more objective decisions in a short period of time, since the information they need will be more clearly and understandably accessible in one place.